Mutational and expressional association of the PIK3CA gene with the risk of breast cancer in the Pakistani population: The PIK3CA gene and breast cancer - Abbasi, Samina Asghar; Khan, Rashida; Ahmed, Mehvish Naseer; Hussain, Kashif; Riaz, Aayesha; Mansoor, Qaisar; Qayyum, Mazhar; Mehmood Baig, Ruqia (Cellular and Molecular Biology, 2023)
PI3K pathway is a very important pathway that is reported to be involved in breast cancer. Mutation of PI3K and p110 alpha-catalytic subunit of phosphatidylinositol 3-kinase (PIK3CA) is of high predictive and prognostic values in breast cancer. The purpose of the current study was to screen the hotspot mutations of the PIK3CA gene i.e. rs2677760, rs3806685, rs121913273 & rs121913279 along with expressional analysis of PI3K and PIK3CA genes in breast cancer female patients. For mutational analysis, TaqMan assay & Sanger sequencing were performed while for expressional analysis real-time PCR was carried out. Mutant allele C of rs2677760 was observed to be high in postmenopausal patients. The frequency of mutant allele G of rs3806685 was significantly high in breast cancer patients. All diseased and control samples were of wild type for the hotspot rs121913273 and rs121913279 with allele G for rs121913273 and A for rs121913279. Expression of the PI3K was high in breast cancer tissue samples as compared to the adjacent controls. While the expression of the thePIK3CA gene was significantly high in premenopausal breast cancer patients. It was concluded that the mutant allele C of rs2677760 might have some sort of association with the menopausal status and it could be used as a diagnostic marker in post-menopausal women if studied further. Mutant allele G of rs3806685 was also found to be associated with breast cancer. While multiallelic rs121913273 and rs121913279 showed a different trend for the studied population. For expressional analysis, PI3K showed over-expression in the cases while PIK3CA gene expression was observed to be significantly associated with pre-menopausal status.